PENGARUH BIAYA PENDIDIKAN TERHADAP HASIL BELAJAR MATA PELAJARAN KEWIRAUSAHAAN SISWA SMK NEGERI 2 PEKANBARU - Setiawan, Edi; Sumarno, Sumarno; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine how much influence the cost of personal education on learning outcomes of SMK Negeri 2 Pekanbaru students on the subjects of entrepreneurship. Learning outcomes SMK Negeri 2 Pekanbaru student forces 2012 at entrepreneurship subjects showed fluctuating circumstances. Of the 28 program skills, there are only 9 programming skills are increased learning outcomes. From 9 program skills is only one programming skill is listed as a program skill with students who have a personal education supreme. The remaining 8 programming skills is not a student with a personal education supreme. The method used is a simple regression analysis with the cost of personal education as independent variables and learning outcomes as the dependent variable. The results of analysis show that the influence of the cost of personal education on learning outcomes of students SMK Negeri 2 Pekanbaru is at 16.5%.Key Words: The cost of personal education, learning outcomes, entrepreneurship